2017
DOI: 10.1016/j.jcis.2017.03.085
|View full text |Cite
|
Sign up to set email alerts
|

The role of surface active species in the fabrication and functionality of edible solid lipid particles

Abstract: Lipid particles are very promising candidates for utilisation as Pickering stabilisers, and fabrication of these species has been attracting considerable academic and industrial research. Nonetheless, current understanding of these systems is hindered by the fact that, as a whole, studies reporting on the fabrication and Pickering utilisation of lipid particles vary significantly in processing conditions being utilised and formulation parameters considered. The present study investigates, under well-controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…The preparation process is fully described elsewhere. 21 Systems were then stored at 4°C until further analysis. Emulsions were fabricated using two emulsification techniques at varying energy inputs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The preparation process is fully described elsewhere. 21 Systems were then stored at 4°C until further analysis. Emulsions were fabricated using two emulsification techniques at varying energy inputs.…”
Section: Methodsmentioning
confidence: 99%
“…The thermal behaviour of the lipid particles has been previously studied and it was demonstrated that it is highly dependent on the type and concentration of the surface active component used. 21 More specifically, melting events commence at ca. 48.2 ± 0.2°C with peak temperatures close to 50.7 ± 0.1°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Journal of Colloid and Interface Science, 2017. 500: p. 228‐240 [9] . (B) Confocal micrograph of an o/w emulsion stabilised by wax particles; red colour represents fluorescence signal from the dyed colloidal wax particles Zafeiri, I., et al, Fabrication, characterisation and stability of oil‐in‐water emulsions stabilised by solid lipid particles: The role of particle characteristics and emulsion microstructure upon Pickering functionality Food & Function, 2017 [10] .…”
Section: Lipid Particles As Pickering Emulsion Stabilisersmentioning
confidence: 99%
“…The melting thermogram of the CLPs shows a small exothermic peak at ~42 °C, which may indicate that the crystals reorganize and recrystallize in a more stable crystalline form. This small exothermic peak is followed by a broad and much bigger endothermic melting peak with a maximum at ~62 °C that consists of a series of distinct smaller peaks indicative of several structured layers melting in multiple events (Zafeiri, Norton, Smith, Norton, & Spyropoulos, 2017).…”
Section: Particle Characterizationmentioning
confidence: 99%